(untitled) (Global Journal of Human-Social Science, 2022)
The positive theories of private liberty penalty attribute to it a various of manifests functions, most of them, contradictory and incompatible with each other, but which have as a common trait the idea of social defense. The present work sought to carry out a critical analysis of the theories that attribute to the private liberty penalty a manifest function that would be able to justified its legitimation.